CLINICAL EFFICACY OF PANCHAMULADI KAAL BASTI IN THE MANAGEMENT OF AMAVATA (RHEUMATOID ARTHRITIS) - Pramod Mandalkar; Rajneesh Baria; Nayan Joshi; Dilip Pandya; Prashant Patil (International Journal of Applied Ayurved Research, 2016)
Amavata has been a challenging problem to the medical field; it can be correlated with Rheumatoid Arthritis (R.A.). Ama and vitiated Vata plays dominant role, though all Dosha take part in the causation of the disease. Various treatment protocols are applied in this disease with partial success. Amavata is such a disease which continues to pose challenge to physician due to severe morbidity and crippling nature. It causes intolerable pain and severe deformities making the patient disable and bed ridden. Many research works have been carried out to solve this clinical enigma. But an effective, safe and less complicated treatment is still required for the management of Amavata. In present clinical study 12 patients of clinically proven Amavata (Rheumatoid Arthritis) were treated with Panchamuladi Kaal Basti to evaluate its efficacy in them. All clinical Nidanadi Ayurvediya parameters & ARA guidelines for Rheumatoid Arthritis were followed. Before treatment & after treatment analysis was done & results were calculated statistically using paired‘t’ test. Results obtained are encouraging & indicate the efficacy of Panchamuladi Kaal Basti over Amavata (Rheumatoid arthritis) exploring many aspects of this clinical entity.